2021
DOI: 10.15587/1729-4061.2021.235882
|View full text |Cite
|
Sign up to set email alerts
|

Development of a solar element model using the method of fractal geometry theory

Abstract: It is shown that in the existing models of the solar cell, assumptions were made about the ideally smooth surface topography, which had a significant impact on the calculation of the output parameters. It is proposed to take into account the real working area of the receiving surface of the solar cell to improve the accuracy, linearity and stability of the current-voltage characteristics. A geometric model of the structure of the receiving surface of a solar cell has been developed, which describes and takes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…or, taking into consideration ratio (12), we obtain the value of the external R ext (47) and the internal R int (48) electrical resistance depending on the applied frequency ω, in accordance with expressions (45) and ( 46): 45), (46), we obtain expressions (49) to (52):…”
Section: At D D S Smentioning
confidence: 65%
See 3 more Smart Citations
“…or, taking into consideration ratio (12), we obtain the value of the external R ext (47) and the internal R int (48) electrical resistance depending on the applied frequency ω, in accordance with expressions (45) and ( 46): 45), (46), we obtain expressions (49) to (52):…”
Section: At D D S Smentioning
confidence: 65%
“…Paper [12] reports results of a study into the surface relief of the material, in the structure of which, under the influence of external factors and damaging defects, local inhomogeneities, micropores, macrocracks are formed. It is shown that such a structure is characterized by fractal properties of self-similarity, scalability, invariance, and can be investigated on the basis of the theory of fractals.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The same area as before will produce more energy [23]. If the PV performance can be increased then the energy produced will increase and the influence of the season can be reduced slightly.…”
Section: Discussion Of Results Influence Of Seasons On Energy Generat...mentioning
confidence: 94%